USTP- Panaon Recompense Waste Management: Automated Segregation and Web-Based Notifications - Hilot, Crichpe A; Beniga, Janjel S; Maca-ambac, Sheena L; Pizana, Marchel P; Amin, Warnner Daminar (MDP Student Conference, 2025)
Recompense Waste Management: Automated Waste Segregation and Web-Based Notifications provides a novel solution to the growing problem in the field of waste management. The system aimed to enhance the segregation and disposal of waste provides automation and a technological approach to it making it efficient, sustainable, and accountable. Functionality The main function is automatically sorting waste, identifying biodegradable and non-biodegradable waste, rejecting expired waste. Smart segregation can be simplified by using smart segregation bins with advanced sensor technology. "Real time update on the bins status is provided through the web-based notification system, which allows enumerators to keep an eye on how much waste the bins have remotely and receive instant notifications for full bins or system errors. This minimizes the necessity for human interventions, resulting in better overall operational efficiency. Methods of evaluation included surveys and rules for system users with statistical analysis of responses. The study also evaluated the system’s use in user studies conducted under controlled conditions. Not only does this inventive solution combat the logistical issues surrounding waste management, but it also promotes recycling and the correct disposal of items through efficient sorting.